EVALUASI KESESUAIAN LAHAN TANAMAN KELAPA (Cocos nicifera L.) DI KECAMATAN SECANGGANG KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Hadi Wijoyo; Silvia Nora; Windi Manullang (UNIVERSITAS LABUHANBATU, 2022)
This research to the characteristics of the land suitability of coconut plantations in the Secanggang District. This research also analyzes the improvement efforts that need to be done in increasing the productivity of coconut plants and make maps of actual land suitability and potential land suitability of coconut plants in Secanggang District. As well as providing recommendations for fertilization on coconut plantations. This research was conducted using a survey method consisting of four stages of activity, namely preparation, main survey, soil analysis and data processing. It can be seen from the results of this study that the potential land suitability of coconut in Secanggang District is S3 f and n (marginally according to nutrient retention factors and nutrient availability) in the Village of Kepala Sungai, Tanjung Ibus, Karang Gading, Perkotaan and Telaga Jernih. S3 f (marginally according to nutrient retention factor) in Karang Anyar, Kebun Kelapa, Secanggang, Selotong, Pantai Gading, and Teluk Village. S2 w, f and n (enough according to the limiting factors of water availability, nutrient retention and nutrient availability) exist in Sei Ular and Hinai Kiri villages. The with improvement efforts to the limiting factor of nutrient retention by adding organic matter, the limiting factor of low nutrient availability is by fertilizing. After an effort has been made to evaluate the suitability of coconut land to S2 w with the limiting factor of water availability, namely rainfall, which is the main limiting factor in assessing land suitability because land improvements cannot be made.